THE INFLUENCE OF THE “SERVICE-BASED LEARNING” METHOD IN ISLAMIC RELIGIOUS EDUCATION TO INCREASE STUDENT EMPATHY AT SDN MAJALENGKA KULON 1 - Hindah Fauzan, Fadhil; Maulana Jamaludin, Gilang (International Journal of Multidisciplinary Reseach, 2025)
This study aims to examine the effect of the implementation of the Service Learning method on increasing student empathy in Islamic Religious Education (PAI) learning at SDN Majalengka Kulon 1. The background of the study departs from the fact that PAI learning in elementary schools is still dominant in the cognitive aspect so that it is less than optimal in developing the affective domain, especially empathy. The research method uses a quantitative approach with a quasi-experimental design of the Non-Equivalent Control Group Design type, which involved 25 students in the experimental group and 25 students in the control group. The instruments used included an empathy questionnaire, an empathic behavior observation sheet, and student reflection notes, which had gone through a validity and reliability testing process. Data analysis was carried out through normality tests, homogeneity tests, t-tests, and gain score calculations. The experimental group recorded an average increase of 20.8 points, while the control group only increased by 5.2 points. The results of the post-test t-test gave a significance value of 0.000 (<0.05), which means there was a significant difference between the two groups after the treatment was given. Student observation and reflection data support these findings, demonstrating that student involvement in social activities enables them to better understand, experience, and directly interpret Islamic Religious Education values. Overall, the ServiceLearning method has proven effective in fostering empathy and social awareness in students through real-life experiences relevant to Islamic principles.